PERENCANAAN PENYEDIAAN FASILITAS PARKIR PADA PUSAT PERBELANJAAN ROXY SQUARE DI KABUPATEN JEMBER” - Dirganakbari, Mh. Iqbal; Hayati, Nunung Nuring; Suyoso, Hernu (FSTPT Indonesia, 2015)
A parking lot is a public facility and supporter for planning of a shopping center. Roxy Square is one of the shopping center in Jember and still managing a parking lot facility. The parking lot facility must be planned with the exact calculation, management, and circulation system in order to prevent a lack of parking zone, a queue and a traffic jam. This research plan a need of the parking lot for vehicle based on SRP and the difference between the destination and the departure of the vehicles. The result of the analysis is obtained a need of the parking lot on the workday is only 35% from weekend. Therefore, a strategy of parking system needed. The area has three parking zones so that an open closed zone system and managemet of an efficiency parking lot for a daily parking need is done.